Digital aroma technology for chemical sensing: temporal chemical images of complex mixtures - Kruglenko, I.V.; Snopok, B.A.; Shirshov, Y.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The reliability of Electronic nose applications is mainly based on the sensitivity, repeatability and discernment properties of the sensors composing the array. Due to nature of the chosen sensitive layers, the sensors are particularly suitable to classify environments in which compounds with various chemical functionality play a key role. This article is focusing on the novel strategy aimed at the improving the quality and quantity of chemical information from the sensing instruments based on incorporation kinetic aspects of the array response for perfect formation and improved discrimination of chemical images of the probes. We describe a procedure for reducing both time response and number of elements of gas sensor arrays based on principal component analysis (PCA). Thus, digital aroma technology may be used not only as background for formation of chemical images using intelligent sensor massifs but as well as effective experimental tools for characterization and selection coatings with desired chemical functionality by using time-resolved pattern recognition.